Equação mestra microscópica para o modelo de Rabi - Lopes, Iury Nunes (2013)
The Rabi model is the most complete one has to describe the interaction between radiation and matter. However, as it is difficult to obtain the exact solution to this model, many of recent atom-field studies have used the Jaynes-Cummings model, which eliminates the "counter rotating" terms from the Rabi Hamiltonian in an approach known as "rotating wave approximation". This approach was very precise to describe many experiments in quantum optics area in the past two decades, especially in the context of cavity quantum electrodynamics, where the atom-field coupling g is very weak compared to the atomic transition frequency ω0 and the cavity field frequency ωc. However, in recent experiments in the context of circuit quantum electrodynamics, the atom-field coupling can be comparable to the atom and field frequencies so that the rotating wave approximation is no longer valid. A first goal of the present work is to examine the validity of the rotating-wave approximation in the context of circuit quantum electrodynamics. We also take into account the dissipation of the system, and to do that we have analyzed two different models: a phenomenological approach where the master equation is derived by adding the free decay of the atom and the field, regardless of the interaction between them, and another microscope, where the master equation is derived by taking into account the interaction between the atom and the field. We then investigate what happens when one has two atoms interacting with the same field in the cavity, considering, for example, the "spontaneous" generation of correlations between the atoms mediated by the field, that is, assuming initially all subsystems (atoms and field) in their ground states, we study the dynamics of correlations generated between the atoms. To quantify those correlations we employ measures as quantum discord and entanglement of formation.